PERIODONTAL DISEASE-SYSTEMIC DISEASE INTER RELATIONSHIP QUESTIONNAIRE STUDY - MEENAKSHI PRIYANKA V,; DR. JAIGANESH RAMAMURTHY, (International Journal of Pharma and Bio Sciences, 2015)
Aim: To determine the awareness among patients about the interrelationship between periodontal and systemic diseases.Method and method: A survey was conducted among 60 patients who visited dental hospital in the form of questionnaire. 12 questions were framed to evaluate the awareness among patients about periodontal and systemic diseases inter relationship. Results: 60 patients were surveyed. About 75% of them were not aware that periodontal disease is correlated with systemic diseases like diabetic mellitus, cardiovascular diseases, haematological disorders, hormonal discrepancies and oeteoporosis. Conclusion: The awareness about the interrelationship of periodontal and systemic diseases among patients is very minimal.